Supplementary honey bee (Apis mellifera L.) pollination enhances fruit growth rate and fruit yield in Paeonia ostii (family: Paeoniaceae) - Zhang, Kaiyue; Li, Yuying; Sun, Kaili; Bao, Junyi; He, Chunling; Hou, Xiaogai (PloS one, 2022)
Insufficient pollination leads to low and unstable production of oil tree peony. Supplementary managed honeybees ( Apis mellifera L.) in agricultural ecosystems is a common practice for addressing the problem. At this study site (N 34°38′30″ and E 112°39′43″, with an altitude of 125.5 m), we set up four pollination areas (low-density bee pollination group (LDBP), high-density bee pollination group (HDBP), blank control group (CK1) and field control group (CK2)) to examine the pollination effectiveness of different densities of honeybee supplementation on oil tree peony ( Paeonia ostii ). Our work demonstrated that bee-pollination increased fruit size and growth rate. On average, bee-pollinated (LDBP) plants produced 63.16% more number of seeds per plant, showed also 53.47% more weight of seeds per plant than those in CK2. Also, seeds of LDBP contained, on average, 26.15% more oil content than CK2. Kernel percent and seed oil fatty acid content, however, were unaffected (F = 1.759, p = 0.074). Compared with LDBP, weight of seeds per plant and oil content with HDBP decreased by 21.89% and 2.63%, respectively. Following the same trend, compared with LDBP, HDBP slowed fruit growth and reduced fruit size. Our results showed that insufficient pollination limits fruit set in oil tree peony, while supplementary reasonable bee density in the field for pollination is an important strategy to maximize fruit yield.